Nasopharyngeal Carcinoma with a Complication of Facial Nerve Paresis (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2021)
Introduction: One fifth of NPC patients have cranial nerve involvement at the time of diagnosis. The nearby location of rossenmuller fossa to lacerum foramen and middle base of the cranium provide way for tumor to extent directly to the cranium and adjacent cranial nerve. Facial palsy due to NPC does not happen very often, with incidence only compromise less than 1% of all cases. Case report: We reported a case of a 42 years old female with a complaint of blood stain rhinorea, mass in the nasopharynx, and facial assymmetry. Based on his history of illness, physical examination, imaging, and histopathology, the working diagnosis was Nasopharyngeal Carcinoma Stage IVA (T4 N0 M0) with facial nerve paresis (Hause-Brackmann V). The intervention done for the patient was radiotherapy.  Conclusion: The patient refused to undergo chemotherapy, so the only therapy done in this case was radiotherapy. After undergoing 35 cycles of radiotherapy, a fair improvement was seen clinically on the patient